1996
DOI: 10.1080/15428119691014305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metalworking Fluid Mist Exposures from Machining with Different Levels of Machine Enclosure

Abstract: This research investigated the efficacy of machine enclosures in reducing employee exposures to metalworking fluid mist. Four hundred fifty-five personal samples from automotive machining and grinding operations collected over six years were divided into three groups based on the type and extent of enclosure and local exhaust ventilation. The sample groups were (1) machining equipment with original equipment manufacturer (OEM) total enclosures and local exhaust ventilation, (2) machining equipment with partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…One of the negative aspects associated with the use of a cutting fluid is health concerns and in particular the inhalation of cutting fluid mist produced during the machining process (Hands et al, 1996). One of the principal mechanisms associated with cutting fluid mist formation is atomization.…”
Section: Introductionmentioning
confidence: 99%
“…One of the negative aspects associated with the use of a cutting fluid is health concerns and in particular the inhalation of cutting fluid mist produced during the machining process (Hands et al, 1996). One of the principal mechanisms associated with cutting fluid mist formation is atomization.…”
Section: Introductionmentioning
confidence: 99%
“…Negative health effects due to dermal contact and fluid mist inhalation have raised concerns regarding the use of cutting fluids, and thus the industrial hygiene community is directing ever more attention to cutting fluid exposure. (3) In addition, fluid splashing, spillage, and the "carrying off" of fluid on metal chips can ultimately lead to inadvertent contamination of groundwater, lakes, and rivers with the fluid as well as metal fines. Upon disposal, the treatment of used fluids prior to introduction into wastewater streams is not totally effective and also represents a significant and increasing cost (in some cases exceeding the purchase price of the fluid).…”
mentioning
confidence: 99%
“…Pre-treatment and treatment of cutting fluids serves to reduce the environmentally damaging influence of the fluid, but does not completely eliminate the potential hazard. In addition to the environmental concerns associated with cutting fluids, several studies have shown that humans exposed to cutting fluids through dermal and inhalation pathways often develop health problems [70]. Motivated by health problems related to cutting fluid mist inhalation, several recent research efforts have focused on investigating the mechanisms associated with cutting fluid mist formation [71].…”
mentioning
confidence: 99%